Are statins effective for primary prevention of CVD?. Issue 5 (May 2016) - Caratao, Makristy; Van Buskirk, John
Abstract : Evidence‐Based Answer : Statin use is effective in lowering rates of cardiovascular disease (CVD) events (stroke and myocardial infarction [MI]) and all‐cause mortality in adult men and women without prior history of CVD events, including in those with low (<10% 5‐year) cardiovascular risk (SOR: A, systematic reviews of RCTs).